Identification and antioxidant activity test of β-tocopherol from Dompu corn oil as anti-aging - Permadi, Adi; Budiastuti, Pramudita; Setyanto, Barry Nur; Wulandana, Rachmadian; Nuraisyah, Fatma; Novitasari, Putri Rachma; Syamsuddin, Arief; Ramadhan, Muhammad Kaisar Sutomo; Rosandy, Andi Rifki (Institute of Advanced Engineering and Science, 2025)
Corn is a well-cultivated food crop that is grown extensively worldwide. The used portion of corn is its seeds, which are rich in oil. The objective of this study is to separate and characterize tocopherol from corn oil in Dompu, Sumbawa by employing spectroscopic techniques such as ultraviolet (UV) spectrophotometry, ultra-performance liquid chromatography (UPLC), nuclear magnetic resonance (NMR), and liquid chromatography-mass spectrometry (LC-MS). Subsequently, the in-vitro antioxidant activity of the tocopherol was assessed. 1 kilogram of dry maize kernels subjected to 70% ethanol extraction yielded 30 grams (35 ml) of corn oil. The purified isolate obtained from the fractionated extract, using radial chromatography, demonstrated the presence of tocopherol. The isolated sample exhibited the presence of beta-tocopherol. Beta-tocopherol's anti-aging properties were assessed by conducting an in-vitro antioxidant activity test utilizing the tyrosinase enzyme. The IC50 value obtained was 83.954±2.849 ppm. The IC50 value indicates that beta-tocopherol possesses significant antioxidant activity, making it suitable for usage as a primary ingredient in cosmetics and pharmaceutical products.